Cardiac-specific knockdown of Bhlhe40 attenuates angiotensin II (Ang II)-Induced atrial fibrillation in mice - Ren, Kai-Wen; Yu, Xiao-Hong; Gu, Yu-Hui; Xie, Xin; Wang, Yu; Wang, Shi-hao; Li, Hui-Hua; Bi, Hai-Lian (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrosis and atrial inflammation are associated with the pathogenesis of atrial fibrillation (AF). Basic helix–loop–helix family member E40 (Bhlhe40) is an important transcription factor, which is involved in tumors, inflammation, apoptosis, viral infection, and hypoxia. However, its role and molecular mechanism in AF remain unclear. In this study, a mouse model of AF was induced by Ang II infusion. The atrial diameter was evaluated using echocardiography. Induction and duration of AF were measured by programmed electrical stimulation. Atrial structural remodeling was detected using routine histologic examinations. Our results showed that Bhlhe40 was significantly upregulated in angiotensin II (Ang II)-stimulated atrial cardiomyocytes and atrial tissues and in tissues from patients with AF. Cardiac-specific knockdown of Bhlhe40 in mice by a type 9 recombinant adeno-associated virus (rAAV9)-shBhlhe40 significantly ameliorated Ang II-induced atrial dilatation, atrial fibrosis, and atrial inflammation, as well as the inducibility and duration of AF. Mechanistically, cardiac-specific knockdown of Bhlhe40 attenuated Ang II-induced activation of NF-κB/NLRP3, TGF-1β/Smad2 signals, the increased expression of CX43, and the decreased expression of Kv4.3 in the atria. This is the first study to suggest that Bhlhe40 is a novel regulator of AF progression, and identifying Bhlhe40 may be a new therapeutic target for hypertrophic remodeling and heart failure.